Les Grands entretiens : cinquante ans d'histoire littéraire (Lire magazine, 2021)
Contient 50 ans d'entretiens littéraires dont Marguerite Yourcenar, Emmanuel Carrère, Margaret Atwood, Philippe Roth, Virginie Despentes, Italo Calvino, Mario Vargas Llosa, Marguerite Duras, Elisabeth Badinter, Jean Echenoz, Roland Barthes, Annie Ernaux, Mary Higgins Clark, Michel Houellebecq, Aimé Césaire, Eugène Ionesco, J.M.G. Le Clézio, Patrick Modiano, Doris Lessing, Edgar Morin, Marie Ndiaye, Jean d'Ormesson, Toni Morrison, Yasmina Reza, Françoise Sagan, Claire Brétécher, Michel Tournier, Joyce Carol Oates, Vladimir Nabokov, Hergé, René Goscinny, etc.